The Associations of Peer-Rated Popularity and Likeability With Dark Triad Personality Traits in Adolescent Groups - Zsolt Péter Szabó; Natália Zsuzsanna Orosz; Réka Gulyás; András Láng (Europe's Journal of Psychology)
One of the most significant challenges in adolescence is the pursuit of social acceptance, which can manifest in various forms, including likeability and popularity. Achieving social acceptance is associated with positive outcomes, while its absence is linked to adverse consequences. Existing research into the personality determinants impacting the ability to elicit likeability or gain popularity remains limited, primarily focusing on the influence of Big Five traits. This study aimed to explore the relationships between self-reported Dark Triad traits -encompassing Machiavellianism, subclinical psychopathy, and subclinical narcissism- and peer-rated likeability and popularity in a naturalistic high school classroom setting. The sample comprised 184 secondary students (98 females, 86 males) with an average age of 16.29 (SD = 1.36). Participants self-reported their Dark Triad traits and provided peer ratings through sociometric questions related to likeability and popularity. Our findings indicated that narcissism was significantly and positively associated with both likeability and popularity. In contrast, psychopathy and Machiavellianism exhibited minimal associations with measures of social acceptance. We discuss the theoretical and practical implications of these findings.